Boundary resource management in innovation ecosystems: The case of e-commerce - Tobias Wulfert (Electronic Markets, 2023)
Major challenges in contemporary information systems development demand new development approaches, such as innovation ecosystems, consisting of a focal innovation platform surrounded by independent developers. The attraction of third-party developers and the amplification of generativity in extension development call for sophisticated boundary resources. As demarcation points between an innovation platform and external developers, boundary resources entail a strategic value and need to be managed carefully. However, existing research does not provide an approach for the holistic management of boundary resources from design to retirement. We apply a design science research approach consisting of two design cycles involving a literature review identifying 26 application lifecycles and the analysis of eight innovation platforms in e-commerce. We evaluated the model for boundary resource management in interviews with nine domain experts. We develop an integrated boundary resource management lifecycle as a specialization of application lifecycle management for the holistic management of boundary resources in innovation ecosystems addressing third-party developers. The boundary resource management lifecycle consists of four layers: boundary resource governance, continuous communication, technical boundary resources, and supplementary boundary resources. It decouples technical and supplementary boundary resources while emphasizing their intertwined nature for ecosystem participants. Owners of innovation platforms can instantiate the reference procedure model for attracting developers.
Keywords: L14; L22; O32; 620; Boundary resources; Innovation platform; Application lifecycle management; E-commerce; Design science research